Basic clinical lab competencies for respiratory care : an integrated approach - White, Gary C. (Delmar, Cengage Learning, 2013)
Combining theoretical knowledge and practical skills, this book emphasizes the importance of assessment of need, contraindications, hazards/complications, monitoring, and outcomes assessment in respiratory care. It offers readers the knowledge and skills needed to practice the art and the science of respiratory care